2021
DOI: 10.1016/j.schres.2021.09.003
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 dimensions and psychotic experiences among US college students: Findings from the Healthy Mind Study 2020

Abstract: Background The COVID-19 pandemic has caused tremendous changes in daily living, which may be related to mental health problems, including psychotic experiences, though research has only begun to assess these associations. Methods We analyzed data from the Healthy Minds Survey (Fall Semester Cohort 2020), which is a non-probability sample of students attending one of 36 universities in the United States, who completed an online survey during the COVID-19 pandemic (Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…At the same time, Oh et al found that other COVID-19 related dimensions, such as financial distress and anxiety, were positively associated with PEs among students. 99 Some authors suggested that the pandemic may be beneficial for mental health of young people withschizotypal symptoms because isolation due to COVID-19 insulates them from social stress. 100 Contrarily, another study found that despite reporting more social avoidance due to the pandemic, schizotypal students exhibited high levels of fear of COVID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, Oh et al found that other COVID-19 related dimensions, such as financial distress and anxiety, were positively associated with PEs among students. 99 Some authors suggested that the pandemic may be beneficial for mental health of young people withschizotypal symptoms because isolation due to COVID-19 insulates them from social stress. 100 Contrarily, another study found that despite reporting more social avoidance due to the pandemic, schizotypal students exhibited high levels of fear of COVID.…”
Section: Discussionmentioning
confidence: 99%
“…The authors explained their findings by the fact that some COVID‐19‐related factors such as increased contact with family members might serve a protective function for students. At the same time, Oh et al found that other COVID‐19 related dimensions, such as financial distress and anxiety, were positively associated with PEs among students 99 . Some authors suggested that the pandemic may be beneficial for mental health of young people withschizotypal symptoms because isolation due to COVID‐19 insulates them from social stress 100 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, college students have reported increased levels of depression, anxiety, substance misuse, and self-harm behaviors linked to financial strain, infection, and loss of a loved one due to COVID ( ElTohamy et al, 2022 ; Oh et al, 2022 ; Oh et al, 2021b ; Oh et al, 2021c ). Experiences of racial discrimination during the pandemic have also been associated with severe depression and psychotic experiences among college students ( Oh et al, 2021a ; Oh et al, 2021c ).…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there is currently only one previous study on caregiving and PE. This large US study including only college students found that caregiving to COVID-19 patients was not significantly associated with PE [ 19 ]. However, the generalizability of this previous study is severely limited, given that the sample was relatively young and highly educated, occurring in the midst of a pandemic in a high-income country.…”
Section: Introductionmentioning
confidence: 99%